2019
DOI: 10.1108/ijesm-05-2018-0009
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of purchasing intentions of energy-efficient products

Abstract: Purpose This paper aims to identify factors affecting consumers’ purchasing intentions of energy-efficient products (energy awareness, perceived benefits, perceived price and consumers’ attitudes). Also, it examines the effect of consumers’ attitudes on purchasing intentions of energy-efficient products (EEP) from households’ perspectives in Jordan. Design/methodology/approach A self-administered survey was hand-delivered to the targeted sample of households in Amman, Jordan. A total of 516 questionnaires we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
25
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(48 citation statements)
references
References 44 publications
7
25
1
1
Order By: Relevance
“…Results are encouraging, and all proposed hypotheses have been accepted. The findings of this study are consistent with the theory of planned behavior, verifying that attitude is an important antecedent of consumers’ purchase intention of energy-efficient home appliances in China (Hua and Wang, 2019), South Korea (Kim and Han, 2010), India (Yadav and Pathak, 2016), Egypt (Mostafa, 2007), Malaysia (Ta et al , 2017) and Jordan (Akroush et al , 2019). In terms of the positive influence of perceived consumer effectiveness on purchase intention of energy-efficient home appliances in Pakistan, the findings of the study support previous researchers’ findings.…”
Section: Conclusion and Discussionsupporting
confidence: 85%
“…Results are encouraging, and all proposed hypotheses have been accepted. The findings of this study are consistent with the theory of planned behavior, verifying that attitude is an important antecedent of consumers’ purchase intention of energy-efficient home appliances in China (Hua and Wang, 2019), South Korea (Kim and Han, 2010), India (Yadav and Pathak, 2016), Egypt (Mostafa, 2007), Malaysia (Ta et al , 2017) and Jordan (Akroush et al , 2019). In terms of the positive influence of perceived consumer effectiveness on purchase intention of energy-efficient home appliances in Pakistan, the findings of the study support previous researchers’ findings.…”
Section: Conclusion and Discussionsupporting
confidence: 85%
“…One reason may be that the selected respondents in that study included those who were not aware of what LED lighting is, while in this study the respondents were households that might have been willing to buy LED lighting. Nevertheless, this study's findings also contradict Akroush et al, 36 whose respondents were households who were familiar with LED lighting. In contrast, Kim et al 37 found price to be positively related to consumer purchase intention, but their study did not focus on LED lighting nor energy-saving devices.…”
Section: Discussioncontrasting
confidence: 97%
“…Even though LED lights are expensive, they last longer and provide greater value than their older alternatives. Leelakulthanit, 35 in her study, found price was not an important determinant in purchasing LED lights among Thailand's communities, while Akroush et al 36 found price was negatively related to consumers' attitudes and purchase intentions towards energy-efficient products among Jordanian households. On the other hand, Kim et al 37 found price to be positively related to consumer purchase intentions.…”
Section: Unified Theory Of Acceptance and Use Of Technologymentioning
confidence: 91%
See 1 more Smart Citation
“…According to Ryu (2018a) who studied the benefit of Fintech adoption, perceived benefit is defined as users' perception of the potential that Fintech usage will result in a positive outcome. Perceived benefits have been utilised as a direct determinant of intention in many studies (Ryu, 2018;Lee, 2009;Akroush et al, 2018). For example, Akroush et al (2018) studied the factors affecting consumers' purchasing intention towards energy-efficient products in Jordan.…”
Section: Effects Of Perceived Benefit On Intention To Use Islamic Crowdfunding Platformsmentioning
confidence: 99%